Screening of fennel (Foeniculum vulgare) accessions for early maturity and high seed and essential oil yields - KALRA, A; GUPTA, A K; KATIYAR, N; SRIVASTAVA, R K; KUMAR, SUSHIL (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1998-99 and 1999-2000 on accessions of Indian lund raees of fennel (Foeniculum vulgare Mill.) to assess the genetic resources for carly maturity, fruit (seed) yield, essential oil content in fruits and essential oil yield in 6 m2 plots armnged in randomized block design. High levels of variability were observed for all the characters. It was possible to identify accessions that mature early ( 0.6 kg/ plot) nnd essential oil (12 g/plot). One of the accessions CIMAP 2202 was early maturing (140 days) and gave higher yield of seeds (0.76 kg/plot) and essential oil (12.1 g/plot).